(untitled) (UNED Research Journal, 2018)
Many methods to prevent bird deaths at windows are ineffective, and some useful methods are expensive or displeasing. Here we offer, for free download, an image that ended bird accidents on large windows near a tropical cloud forest area, and propose hypotheses for its experimental evaluation